Hard carbon-based composite material and preparation method thereof

By depositing multi-walled carbon nanotubes in situ on the surface of bamboo-based hard carbon particles to form hard carbon composites, the problems of poor conductivity and low sodium storage capacity of existing hard carbon composites are solved, and the high rate performance, long cycle life and high safety of sodium ion batteries are achieved.

CN119542402APending Publication Date: 2025-02-28LONGMEN LAB
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411780386.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing hard carbon-based composite materials have poor conductivity, large specific surface area and high porosity in sodium ion batteries, making it difficult to achieve high reversible storage of sodium ions, poor battery rate performance, short cycle life, and low Coulomb efficiency for the first time.

Method used

By depositing multi-walled carbon nanotubes in situ on the surface of bamboo-based hard carbon particles with rich closed-cell structures, a hard carbon-based composite material is formed, which improves the conductivity and sodium storage capacity of the material.

Benefits of technology

It significantly reduces the electrode resistance, improves the rate performance and cycle life of sodium ion batteries, and enhances the first Coulomb efficiency and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542402A_ABST
    Figure CN119542402A_ABST
Patent Text Reader

Abstract

The invention discloses a hard carbon-based composite material and a preparation method thereof, the hard carbon-based composite material is composed of hard carbon particles and multi-walled carbon nanotubes growing on the surfaces of the hard carbon particles, and the hard carbon particles are bamboo-based hard carbon with rich closed pore structures. The average particle size of the hard carbon particles is 6-8 [mu] m, and the hard carbon particles are obtained through high-temperature carbonization at 1300 DEG C for 2 hours. After nanometer iron oxide is deposited on the surfaces of the hard carbon particles, paraffin is subjected to catalytic cracking for 30 min at the temperature of 600-800 DEG C, and the multi-walled carbon nanotubes can be deposited on the surfaces of the hard carbon particles in situ. The hard carbon-based composite material can be used in the energy storage field of sodium ion battery negative electrode materials and the like. The preparation method is low in raw material cost, short in preparation period and beneficial to large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery energy storage, in particular to a hard carbon-based composite material and a preparation method thereof. Background Art

[0002] With the rapid advancement of my country's "dual carbon" goals, my country is vigorously developing clean and sustainable energy such as solar energy and wind energy. Its purpose is first to reduce carbon emissions. However, clean energy often has the disadvantage of instability, so corresponding energy storage batteries must be configured to achieve "peak shaving and valley filling". Currently, commercial lithium-ion batteries have the advantages of high energy density and mature technology, but they also face disadvantages such as tight lithium metal resources, high prices, and great safety hazards. They face many challenges in commercial large-scale energy storage. Compared with lithium-ion batteries, sodium-ion batteries have the advantages of abundant raw material resources, low cost, and high safety. Although their energy density is not very high, they are very suitable for large-scale energy storage applications.

[0003] As the negative electrode of sodium ion batteries, hard carbon materials have demonstrated high reversible specific capacity (~300mAh / g) and low sodium storage potential (platform voltage is around 0.1V). At the same time, hard carbon materials also have the advantages of wide sources, low cost and no pollution to the environment, making them sodium ion battery negative electrode materials with commercial application prospects.

[0004] However, due to its poor conductivity, large specific surface area and high porosity, single hard carbon materials cannot achieve high reversible storage of sodium ions when used as negative electrode materials for sodium ion batteries. In addition, the diffusion kinetics of sodium ions in such hard carbons are slow, that is, the ion transport path is long and the transport speed is slow, resulting in poor rate performance, short cycle life and low first coulombic efficiency of the assembled battery, which seriously hinders the practical application of hard carbon materials in sodium ion batteries. In order to overcome the above defects, some hard carbon-based composite materials have emerged that require surface modification or new material composites, but such composite materials still have problems.

[0005] For example, the invention patent with publication number CN113948681A discloses a biomass-based hard carbon compound composite material and its preparation method and use. This technical solution mixes the biomass, salt, metal / non-metallic elements used by simple mechanical ball milling. Therefore, the biomass-based hard carbon composite material prepared by high-temperature sintering cannot be effectively carbon-coated, and it is difficult to form a uniform and stable coating. In addition, there are many steps, and the initial efficiency in sodium ion batteries is relatively low.

[0006] In summary, a new hard carbon-based composite material and a corresponding preparation method still need to be developed to solve the problems existing in hard carbon-based composite materials. Summary of the invention

[0007] In order to solve the deficiencies in the prior art, the present invention provides a hard carbon-based composite material and a preparation method thereof, wherein the hard carbon-based composite material is composed of hard carbon and multi-walled carbon nanotubes grown on the surface thereof, wherein the hard carbon is bamboo-based hard carbon with a rich closed-pore structure. The composite material is applied to the negative electrode of a sodium ion battery, which can significantly reduce the electrode resistance and improve the rate performance.

[0008] In order to achieve the above object, the specific scheme adopted by the present invention is: On the one hand, the present invention provides a hard carbon-based composite material, characterized in that the hard carbon-based composite material is composed of hard carbon and multi-walled carbon nanotubes grown on its surface, and the hard carbon is a bamboo-based hard carbon with a rich closed-pore structure. Among them, multi-walled carbon nanotubes have the advantages of excellent conductivity and loose stacking, which can achieve rapid deintercalation of sodium ions, but their own sodium storage capacity is low; the hard carbon refers to non-graphitizable carbon, which has poor conductivity, and its capacity is closely related to the pore structure, especially the closed-pore structure. The present invention prepares a hard carbon-based composite material with high conductivity and high sodium storage capacity through in-situ composite of the two.

[0009] Furthermore, the preparation method of the bamboo-based hard carbon is: Step (1), using bamboo as a precursor, washing, crushing and drying to prepare bamboo particles with a particle size of 3-5 cm; Step (2), pre-carbonizing the bamboo particles in a nitrogen atmosphere at 500° C. for 2-4 hours; Step (3), crushing, grinding and screening the pre-carbonized bamboo carbon particles to obtain bamboo carbon powder with an average particle size of 6-8 μm; Step (4), soaking the bamboo carbon powder in an acid solution with a concentration of 0.1-0.5 mol / L, and then washing and drying; Step (5), carbonizing the dried bamboo carbon powder in an argon atmosphere at 1300° C. for 1-3 hours to obtain bamboo-based hard carbon with a rich closed-pore structure.

[0010] Furthermore, in step (4), the acid solution is any one of hydrochloric acid, nitric acid or sulfuric acid.

[0011] Furthermore, in step (5), the heating rate is 2-8°C / min.

[0012] On the other hand, the present invention provides a method for preparing a hard carbon-based composite material, characterized in that it mainly comprises the following steps: Step 1: Evenly mix N,N-dimethylformamide and deionized water in a volume ratio of 8:2 to obtain a solution A; Step 2: Add bamboo-based hard carbon into solution A and stir thoroughly; Step 3, adding ferrous chloride hexahydrate and anhydrous sodium acetate to solution A, stirring and dissolving to obtain solution B, heating solution B to 90° C. and keeping warm, stirring sufficiently, filtering, washing and drying to obtain an intermediate product, wherein the intermediate product consists of hard carbon and nano-iron oxide deposited on the surface of the hard carbon; Step 4: Evenly mix the intermediate product and solid paraffin powder to obtain a mixture C, in which the mass percentage of solid paraffin powder is 5-15%. Then, add the mixture C into a metal high-pressure container and seal the container. Rapidly place the metal high-pressure container in a high-temperature furnace preheated to 600-700°C and keep it warm for 30 minutes. Under the catalysis of nano-iron oxide, the gas decomposed from the paraffin grows multi-walled carbon nanotubes in situ on the surface of the hard carbon particles. After cooling to room temperature, a hard carbon-based composite material is obtained.

[0013] Furthermore, in step 2, the concentration of hard carbon relative to solution A is 6 mg~12 mg / mL.

[0014] Furthermore, in step 3, the concentration of ferrous chloride hexahydrate relative to solution A is 8-12 mg / mL, and the concentration of anhydrous sodium acetate relative to solution A is 15 mg-25 mg / mL.

[0015] Furthermore, in step three, the drying conditions are: drying at 70° C. for 24 hours.

[0016] Furthermore, in step 4, the high temperature furnace is any one of a tube furnace, a box furnace, and a vacuum furnace.

[0017] Beneficial effects: (1) The present invention combines the high sodium storage properties of hard carbon and the high electrical conductivity of multi-walled carbon nanotubes, deposits multi-walled carbon nanotubes in situ on the surface of hard carbon particles, and obtains a new type of hard carbon-based composite material. By increasing the electrical conductivity of the material through the multi-walled carbon nanotubes grown on the surface of hard carbon particles, the overall resistance of the produced electrode can be reduced, which is convenient for high current charging and discharging. The reduced resistance makes the sodium battery less prone to thermal runaway and improves safety. It can also be used in the field of conductive plastic additives to improve the conductivity of composite materials.

[0018] (2) The present invention uses bamboo-based hard carbon from cheap moso bamboo to prepare a hard carbon-based composite material through a simple method, which has low energy consumption, low cost, short cycle, and is conducive to large-scale production.

[0019] (3) The hard carbon-based composite material prepared by the present invention has a rich closed-pore structure and a large closed-pore size, which is conducive to achieving high specific capacity, high first coulomb efficiency and excellent cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1This is a SEM image of the intermediate product prepared in Example 1 of the present invention at a low magnification.

[0021] Figure 2 This is a SEM image of the intermediate product prepared in Example 1 of the present invention at a high magnification.

[0022] Figure 3 This is a SEM image of the hard carbon-based composite material prepared in Example 1 of the present invention at a low magnification.

[0023] Figure 4 This is a SEM image of the hard carbon-based composite material prepared in Example 1 of the present invention at a high magnification.

[0024] Figure 5 This is a charge and discharge curve diagram of the hard carbon-based composite material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0026] The invention discloses a hard carbon-based composite material and a preparation method thereof. The hard carbon-based composite material consists of hard carbon and multi-walled carbon nanotubes grown on the surface of the hard carbon. The hard carbon is bamboo-based hard carbon with abundant closed-pore structure.

[0027] A method for preparing a hard carbon-based composite material mainly comprises the following steps: Step 1, preparing bamboo-based hard carbon; (1) Using bamboo as a precursor, the bamboo particles are prepared into 3-5 cm bamboo particles after water washing, crushing and drying; (2) Pre-carbonizing the bamboo particles in a nitrogen atmosphere at 500°C for 2-4 hours; (3) crushing, grinding and sieving the pre-carbonized bamboo charcoal particles to obtain bamboo charcoal powder with an average particle size of 6-8 μm; (4) Soak the bamboo carbon powder in an acid solution with a concentration of 0.1-0.5 mol / L (any one of hydrochloric acid, nitric acid or sulfuric acid, which can effectively remove soluble metals as impurities in the bamboo carbon powder, thereby increasing the sodium storage capacity of the hard carbon), and then wash and dry it; (5) The dried bamboo carbon powder is heated to 1300°C in an argon atmosphere at a heating rate of 2-8°C / min and kept at this temperature for 1-3h for carbonization to obtain a bamboo-based hard carbon with a rich closed-pore structure; Step 2: Evenly mix N,N-dimethylformamide (DMF) and deionized water in a volume ratio of 8:2 to obtain solution A; Step 3: Add bamboo-based hard carbon to solution A and stir thoroughly; the concentration of hard carbon relative to solution A is 6 mg to 12 mg / mL; Step 4: Add ferrous chloride hexahydrate and anhydrous sodium acetate to solution A, stir and dissolve to obtain solution B, wherein the concentration of ferrous chloride hexahydrate relative to solution A is 8-12 mg / mL, and the concentration of anhydrous sodium acetate relative to solution A is 15 mg-25 mg / mL; pour solution B into a 90°C water bath for magnetic stirring, filter, wash and dry (dry at 70°C for 24 hours) to obtain an intermediate product, wherein the intermediate product consists of hard carbon and nano-iron oxide deposited on the surface of the hard carbon; Step 5: Evenly mix the intermediate product and solid paraffin powder to obtain a mixture C, wherein the mass percentage of solid paraffin powder in the mixture C is 5-15%, and then add the mixture C into a metal high-pressure container and seal the container, and quickly place the metal high-pressure container in a high-temperature furnace (any one of a tube furnace, a box furnace, and a vacuum furnace) preheated to 600-700°C for 30 minutes, and cool to room temperature to obtain a hard carbon-based composite material. At high temperatures, paraffin catalytic cracking generates multi-walled carbon nanotubes in situ, which are evenly distributed on the surface of hard carbon and are tightly bound to hard carbon in the form of covalent bonds, which is beneficial to electronic conductivity and ion conduction during the process of electrode sodium deintercalation.

[0028] The present invention will be further described below in conjunction with the accompanying drawings and specific implementation methods.

[0029] Example 1 This embodiment discloses a method for preparing a hard carbon-based composite material, which mainly comprises the following steps: Step 1, preparing bamboo-based hard carbon; (1) Using bamboo as a precursor, the bamboo particles are prepared into 3-5 cm bamboo particles after water washing, crushing and drying; (2) Load the bamboo particles into a carbonization furnace, heat to 500°C in a nitrogen atmosphere and keep the temperature for 3 hours for pre-carbonization; (3) The pre-carbonized bamboo charcoal particles are subjected to air flow crushing, grinding and screening to obtain bamboo charcoal powder with an average particle size of 6-8 μm; (4) Soak 1 kg of bamboo carbon powder in 0.1 mol / L nitric acid for 24 h, then wash and dry; (5) The dried bamboo carbon powder is heated to 1300°C in an argon atmosphere at a heating rate of 5°C / min and kept at this temperature for 2 h for carbonization to obtain a bamboo-based hard carbon with a rich closed-pore structure; Step 2: Weigh 8 mL of N,N-dimethylformamide and 2 mL of deionized water, mix well to obtain solution A; Step 3: Add 60 mg of the bamboo-based hard carbon prepared in step 1 to solution A prepared in step 2 and stir thoroughly; Step 4: Add 100 mg of ferrous chloride hexahydrate and 200 mg of anhydrous sodium acetate to solution A, stir magnetically for 15 minutes at room temperature to obtain solution B; pour solution B into a 90°C water bath for magnetic stirring reaction, the stirring speed is 400 rpm, and the stirring reaction time is 4 hours. After the reaction is completed, filter and clean with water and alcohol, and place in an oven at 70°C for 24 hours to obtain an intermediate product, which is composed of hard carbon and nano-iron oxide deposited on the surface of the hard carbon; Step 5. Mix 9 g of the intermediate product and 1 g of solid paraffin powder evenly to obtain a mixture C. Then add the mixture C into a metal high-pressure container with a total volume of 500 mL, seal the container, and quickly place the metal high-pressure container in a tubular furnace preheated to 600°C for 30 minutes. Cool to room temperature to obtain a hard carbon-based composite material.

[0030] in, Figure 1 and Figure 2 (Different magnifications) is the SEM image of the intermediate product prepared in step 4. As can be seen from the image, nano iron oxide particles can be seen deposited on the surface of the hard carbon. Figure 3 and Figure 4 (Different magnifications) are SEM images of the hard carbon-based composite material prepared in step five, where multi-walled carbon nanotubes grown on the surface of the hard carbon particles can be seen.

[0031] The hard carbon-based composite material prepared in this example was used as the working electrode, sodium metal as the counter electrode, glass fiber membrane as the diaphragm, and 1M NaPF6 propylene carbonate (PC) / ethyl methyl carbonate (EMC) solution as the electrolyte. The charge and discharge test (current density 30 mA / g, voltage range 0.005~2 V) was carried out. The charge and discharge curves are shown in FIG. Figure 5 As shown in the figure, the first charge capacity can reach 294.9mAh / g at 0.1C, and the first storage efficiency is 87.95%; after 100 cycles, the capacity retention rate is 97.1%, and the charge capacity reaches 252.1mAh / g at 1C.

[0032] Example 2 This embodiment discloses a method for preparing a hard carbon-based composite material, which mainly comprises the following steps: Step 1, preparing bamboo-based hard carbon; (1) Using bamboo as a precursor, the bamboo particles are prepared into 3-5 cm bamboo particles after water washing, crushing and drying; (2) Load the bamboo particles into a carbonization furnace, heat to 500°C in a nitrogen atmosphere and keep the temperature for 3 hours for pre-carbonization; (3) The pre-carbonized bamboo charcoal particles are subjected to air flow crushing, grinding and screening to obtain bamboo charcoal powder with an average particle size of 6-8 μm; (4) Soak 1 kg of bamboo charcoal powder in 0.2 mol / L hydrochloric acid for 24 h, then wash and dry; (5) The dried bamboo carbon powder is heated to 1300°C in an argon atmosphere at a heating rate of 5°C / min and kept at this temperature for 2 h for carbonization to obtain a bamboo-based hard carbon with a rich closed-pore structure; Step 2: Weigh 8 mL of N,N-dimethylformamide and 2 mL of deionized water, mix well to obtain solution A; Step 3: Add 60 mg of bamboo-based hard carbon into solution A and stir thoroughly; Step 4: Add 100 mg of ferrous chloride hexahydrate and 200 mg of anhydrous sodium acetate to solution A, stir magnetically for 15 minutes at room temperature to obtain solution B; pour solution B into a 90°C water bath for magnetic stirring reaction, the stirring speed is 400 rpm, and the stirring reaction time is 4 hours. After the reaction is completed, filter and clean with water and alcohol, and place in an oven at 70°C for 24 hours to obtain an intermediate product, which is composed of hard carbon and nano-iron oxide deposited on the surface of the hard carbon; Step 5. Mix 9.5 g of the intermediate product and 0.5 g of solid paraffin powder evenly to obtain a mixture C. Then add the mixture C into a metal high-pressure container with a total volume of 500 mL and seal the container. Quickly place the metal high-pressure container in a tubular furnace preheated to 700°C and keep it warm for 30 minutes. Cool it to room temperature to obtain a hard carbon-based composite material.

[0033] The same test method as in Example 1 was used to test and the following results were obtained: the first charge capacity at 0.1C could reach 300.2 mAh / g, and the first storage efficiency was 87.8%; after 100 cycles, the capacity retention rate was 95.4%, and the charge capacity at 1C reached 249.3 mAh / g.

[0034] Example 3 This embodiment discloses a method for preparing a hard carbon-based composite material, which mainly comprises the following steps: Step 1, preparing bamboo-based hard carbon; (1) Using bamboo as a precursor, the bamboo particles are prepared into 3-5 cm bamboo particles after water washing, crushing and drying; (2) Load the bamboo particles into a carbonization furnace, heat to 500°C in a nitrogen atmosphere and keep the temperature for 3 hours for pre-carbonization; (3) The pre-carbonized bamboo charcoal particles are subjected to air flow crushing, grinding and screening to obtain bamboo charcoal powder with an average particle size of 6-8 μm; (4) Soak 1 kg of bamboo carbon powder in 0.5 mol / L sulfuric acid for 24 h, then wash and dry; (5) The dried bamboo carbon powder is heated to 1300°C in an argon atmosphere at a heating rate of 5°C / min and kept at this temperature for 2 h for carbonization to obtain a bamboo-based hard carbon with a rich closed-pore structure; Step 2: Weigh 8 mL of N,N-dimethylformamide and 2 mL of deionized water, mix well to obtain solution A; Step 3: Add 60 mg of bamboo-based hard carbon into solution A and stir thoroughly; Step 4: Add 100 mg of ferrous chloride hexahydrate and 200 mg of anhydrous sodium acetate to solution A, stir magnetically for 15 minutes at room temperature to obtain solution B; pour solution B into a 90°C water bath for magnetic stirring reaction, the stirring speed is 400 rpm, and the stirring reaction time is 4 hours. After the reaction is completed, filter and clean with water and alcohol, and place in an oven at 70°C for 24 hours to obtain an intermediate product, which is composed of hard carbon and nano-iron oxide deposited on the surface of the hard carbon; Step 5. Mix 8.5 g of the intermediate product and 1.5 g of solid paraffin powder evenly to obtain a mixture C. Then add the mixture C into a metal high-pressure container with a total volume of 500 mL, seal the container, and quickly place the metal high-pressure container in a tubular furnace preheated to 650°C for 30 minutes. Cool to room temperature to obtain a hard carbon-based composite material.

[0035] The same test method as in Example 1 was used to test and the following results were obtained: the first charge capacity at 0.1C could reach 305.7 mAh / g, and the first storage efficiency was 86.9%; after 100 cycles, the capacity retention rate was 94.6%, and the charge capacity at 1C reached 247.5 mAh / g.

[0036] The above is only a preferred embodiment of the present invention, and does not limit the present invention in any form. Any equivalent changes or modifications made according to the essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A hard carbon-based composite material, characterized in that: The hard carbon-based composite material consists of hard carbon and multi-walled carbon nanotubes grown on the surface of the hard carbon, and the hard carbon is bamboo-based hard carbon with abundant closed-pore structure.

2. A hard carbon-based composite material according to claim 1, characterized in that: The preparation method of the bamboo-based hard carbon is: Step (1), using bamboo as a precursor, washing, crushing and drying to prepare bamboo particles with a particle size of 3-5 cm; Step (2), pre-carbonizing the bamboo particles in a nitrogen atmosphere at 500° C. for 2 to 4 hours; Step (3), crushing, grinding and screening the pre-carbonized bamboo carbon particles to obtain bamboo carbon powder with an average particle size of 6-8 μm; Step (4), soaking the bamboo carbon powder in an acid solution with a concentration of 0.1-0.5 mol / L, and then washing and drying; Step (5), carbonizing the dried bamboo carbon powder in an argon atmosphere at 1300° C. for 1 to 3 hours to obtain bamboo-based hard carbon with a rich closed-pore structure.

3. A hard carbon-based composite material according to claim 2, characterized in that: In step (4), the acid solution is any one of hydrochloric acid, nitric acid or sulfuric acid.

4. A hard carbon-based composite material according to claim 2, characterized in that: In step (5), the heating rate is 2-8°C / min.

5. A method for preparing a hard carbon-based composite material, characterized in that: The main steps are as follows: Step 1: Evenly mix N,N-dimethylformamide and deionized water in a volume ratio of 8:2 to obtain a solution A; Step 2: Add bamboo-based hard carbon into solution A and stir thoroughly; Step 3: Add ferrous chloride hexahydrate and anhydrous sodium acetate to solution A, stir and dissolve to obtain solution B, pour solution B into a 90° C. water bath for magnetic stirring, filter, wash and dry to obtain an intermediate product, which consists of hard carbon and nano-iron oxide deposited on the surface of the hard carbon; Step 4: Evenly mix the intermediate product and solid paraffin powder to obtain a mixture C, in which the mass percentage of solid paraffin powder in the mixture C is 5-15%. Then, add the mixture C into a metal high-pressure container and seal the container. Rapidly place the metal high-pressure container in a high-temperature furnace preheated to 600-700°C and keep it warm for 30 minutes. Cool it to room temperature to obtain a hard carbon-based composite material.

6. The method for preparing a hard carbon-based composite material according to claim 5, characterized in that: In step 2, the concentration of hard carbon relative to solution A is 6 mg to 12 mg / mL.

7. The method for preparing a hard carbon-based composite material according to claim 5, characterized in that: In step 3, the concentration of ferrous chloride hexahydrate relative to solution A is 8-12 mg / mL, and the concentration of anhydrous sodium acetate relative to solution A is 15 mg-25 mg / mL.

8. The method for preparing a hard carbon-based composite material according to claim 5, characterized in that: In step 3, the drying condition is: drying at 70° C. for 24 h.

9. The method for preparing a hard carbon-based composite material according to claim 5, characterized in that: In step 4, the high temperature furnace is any one of a tube furnace, a box furnace, and a vacuum furnace.

Citation Information

Patent Citations

  • Biomass-based hard carbon compound composite material as well as preparation method and application thereof

    CN113948681A